Caracterização geotermobarométrica dos metabasitos de Cajamar (SP), Grupo São Roque, Cinturão Ribeira - De Oliveira, Marcos Aurélio Farias [UNESP]; De Melo, Rodrigo Prudente [UNESP]; Nardy, Antônio José Ranalli [UNESP]; Arab, Paola Bruno (My University, 2011)
Metamafic orthoderivate rocks, characterized by MORB signatures and paleoproterozoic ages occur in Cajamar region central east part of São Paulo State, Brazil. They are associated to philites, metasandstones and metalimestones of São Roque Group volcanosedimentary sequence, Southeastern portion of the Ribeira Belt. For the metamafic rocks the assemblage of metamorphic peak is represented by actinolitealbite- epidote-chlorite typical of regional metamorphism, greenschist facies. For a good characterization of P and T parameters of metamorphism microprobe analyses of main minerals were performed. Metamorphism did not destroy completely the primary mineralogy of original basalt and microgabbro, and augite crystals are registered in many samples, preserved together with metamorphic assemblage, and possibly indicate that the igneous temperatures of crystallization are between 900 and 1.100°C. Textures of mineral equilibrium for the peak paragenesis are not always present in the studied samples. It may be partially caused by the superposition of retrometamorphic events that is a consequence of regional shearing process. Where the equilibrium is reached, chiefly in the occurrences in the south of the area temperature and pressure determinations indicate values close to 487 ± 42°C and 8,2 ± 2.0 kbar, respectively. Other values for P and T lower than that of the peak were also obtained in central and north portion of the area and they are: 450 ± 68°C for T e 4.7 kbar for P and 315 ± 26°C for T and 3.0 kbar for P and may indicate that the mineral equilibrium was not reached in these samples or that they represent the retrometamorphic event. As a concluding remark considering the metamorphic P-T path now obtained one can say that the exhumation process in this area occurred by isothermal decompression.
Geothermobarometric characterization of metabasic rocks of cajamar region (sp): São roque group, ribeira belt
Keywords: Actinolite-albite-epidoto-chlorite assemblage; Greenschist regional metamorphism; Metamafic rocks; Ribeira Belt; São Roque Group; Southeastern Brazil